Transfer and application of the eco-service concept in UK manufacturing companies : an exploratory study - Cook, Matthew Brian (Cranfield University, 2002)
Increasingly, services are utilised by manufacturing companies to satisfy demand. This trend is thought by a number of authors to provide opportunities to develop products that satisfy demand at increased resource efficiencies. This thesis considers a special category of services which have been conceptualised by academics and policy makers to realise this - Eco-services Eco-services have been the focus of a number of research projects lead by those practicing and associated with cleaner product design. This work has mainly focused on product policy and whilst a considerable body of knowledge has been accumulated, the array of factors that would lead to the successful transfer (from academia and to UK manufacturing companies) of this exogenous concept were unknown. This thesis sought to identify and understand these. Two inter linked phases of research were initiated and completed. The first was inductive in nature and was comprised of a Pilot Study. In this data was elicited from a variety of sources so as to provide a robust foundation of knowledge upon which subsequent enquiry could be initiated. It concluded with the construction of an initial conceptual framework which described the attributes of receptivity that were found in UK manufacturing firms to be specific to the Eco-service concept. Also, a number of research propositions were generated so as to guide research in phase two. The second deductive phase of research was undertaken so as to test the initial conceptual framework. A Main Study was carried out in order to elicit primary qualitative data from two UK manufacturing companies. This work was guided by the research propositions and a more in-depth understanding of the attributes of receptivity was gained. This body of knowledge was utilised to refine the initial conceptual framework. This research identified and understood the range of factors that give rise to the successful inward transfer of the Eco-service concept in U manufacturing companies. Eight attributes of receptivity were identified and described in the final conceptual framework. The intention of this work was not to refute current trajectories of research within the Eco-service domain, but rather to provide an additional body of knowledge that can be thought to enable those authors in the Eco-service domain to realise the opportunity that the emergent trajectory of services provides to significantly improve resource efficiencies.